Compilation of the design principles of the child-friendly neighborhood park with the aim of increasing children's creativity - Mohadeseh Mohammadpoor; Shahab Abbaszadeh (مهندسی و مدیریت ساخت)
Children have a special importance among human groups and are considered the greatest wealth of any country. During the second half of the 20th century, a fundamental change occurred in the transformation of rural dwellers into urban dwellers, so that today most children grow up in the man-made space of cities. and on the other hand, the existing restrictions in big cities have led to the expansion of residential complexes and the reduction of the share of private courtyards in contemporary architecture. It seems that the field of mobility and self-expression of children, especially in today's big cities, is becoming more limited day by day. In the basics of urban design, the child is always considered as one of the influential factors in the urban space. But despite this attention, when the defenders of these principles step into the field of design, they forget the children and do not pay any attention to them. The result of this neglect is a depressing and boring city for the residents of small cities, so this research seeks to compile the principles of designing a child-friendly park. The current research is of a qualitative type and the research method used in this research is descriptive-analytical and based on library studies and questionnaires and interpretation of children's drawings and a survey of parents. The results indicate that the strategy of addressing the child in the environment has the highest priority, and strategies such as using children's participation and deciding on their desired neighborhood, using furniture in the child's scale, and using happy colors in the space can be important in this regard.